1927
DOI: 10.1113/expphysiol.1927.sp000433
|View full text |Cite
|
Sign up to set email alerts
|

On the Act of Blinking

Abstract: 1. It is shown, by an investigation of the movements of blinking in the normal individual, that the distribution of interblink periods (intervals between successive blinks measured in seconds) is remarkably constant for the individual under constant experimental conditions. 2 The movements are not reflex, and do not depend on the integrity of the second, third, fourth, fifth, or sixth cranial nerves. They are centrally controlled, and dependent on intermittent impulses passing from the region of the basal gang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
188
2
5

Year Published

1940
1940
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 288 publications
(204 citation statements)
references
References 0 publications
9
188
2
5
Order By: Relevance
“…However, in our paradigm the concurrent recording of skin conductance during the task showed no significant difference between the mean SCL during the negative vs. positive affect condition, thus ruling out a simple interpretation in terms of changes in tonic arousal across these two affective conditions. Because our results also showed a sharp increase of the spontaneous eye blink rate following the presentation of negative (as opposed to positive) feedbacks, changes in early sensory processing in V1 may be interpreted as resulting from an enhanced stress response in this condition (Karson, 1983;Ponder and Kennedy, 1927). The spontaneous eye-blink rate has been linked indirectly to levels of dopamine activity as a state-dependent measure (Barbato et al, 2000;Taylor et al, 1999): the substantial increase in the blink rate following the presentation of negative performance feedbacks may thus reflect a phasic change in levels of dopamine, in particular in the frontal cortex (Abercrombie et al, 1989;Pani et al, 2000, for a review).…”
Section: Likely Sources Of Affective Sensory Filtering In V1mentioning
confidence: 51%
See 1 more Smart Citation
“…However, in our paradigm the concurrent recording of skin conductance during the task showed no significant difference between the mean SCL during the negative vs. positive affect condition, thus ruling out a simple interpretation in terms of changes in tonic arousal across these two affective conditions. Because our results also showed a sharp increase of the spontaneous eye blink rate following the presentation of negative (as opposed to positive) feedbacks, changes in early sensory processing in V1 may be interpreted as resulting from an enhanced stress response in this condition (Karson, 1983;Ponder and Kennedy, 1927). The spontaneous eye-blink rate has been linked indirectly to levels of dopamine activity as a state-dependent measure (Barbato et al, 2000;Taylor et al, 1999): the substantial increase in the blink rate following the presentation of negative performance feedbacks may thus reflect a phasic change in levels of dopamine, in particular in the frontal cortex (Abercrombie et al, 1989;Pani et al, 2000, for a review).…”
Section: Likely Sources Of Affective Sensory Filtering In V1mentioning
confidence: 51%
“…We used the bipolar vertical electro-oculogram (VEOG), continuously recorded during the whole experiment, to quantify the spontaneous eye-blink rate, used as an indirect measure of anxiety (Karson, 1983;Ponder and Kennedy, 1927). Eye-blinks were automatically detected using the Brain-Vision Analyzer ocular correction algorithm during each of the six test blocks and analyzed using a 3x2 repeated measures ANOVA with Affective Condition (NF, PF) and Order (First block, Second Block, Third Block) as within-subjects factors.…”
Section: Data Reduction and Analysismentioning
confidence: 99%
“…Following this line of thought, one can assume that if exogenous blink-generating stimuli are eliminated (e.g., as a result of anaesthesia or in constant environmental conditions), then the central control should define the blink behavior. Furthermore, if the central blink generator with a stationary pace rate is in operation, then the generator will determine the intervals between blinks, though the intervals will still show some random fluctuations (Ponder & Kennedy, 1927;Naase, et al 2005). …”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Ivry and Richardson (2002) suggested that motor commands for bimanual tapping coming from two hemispheres are integrated for the control of the coordinated behavior. The eyelid movements are generated and controlled centrally, but they are also influenced via certain "secondary paths" (Ponder & Kennedy, 1927). On the other hand, the neural pathways responsible for tapping may cross talk to these "secondary paths" leading to the entrainment of blinks.…”
Section: Tapping and Blinkingmentioning
confidence: 99%
See 1 more Smart Citation